USE OF TRANSLATION STRATEGIES IN WRITING: ADVANCED EFL STUDENTS - Murtisari, Elisabet Titik (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
This qualitative study examines how advanced EFL learners use translation in writing, its perceived effects on their written product, and their feelings concerning its use. As translation is generally associated with less competent students, this research focuses on high-level ones. Involving 29 advanced EFL students from a reputable English language faculty in Indonesia, the study collected data through questionnaires using close and open-ended questions. This research demonstrated that, although employed less, translation was still a crucial means for scaffolding among the students. It was shown that creating short chunks in L1 for subsequent translation was the most common strategy while all the participants also self-reportedly practiced mental translations from L1 to L2 in various degrees. This resort to translation often seemed inevitable, but students revealed having mixed feelings towards the use of the interlingual strategy. This study highlights the need to develop awareness among language learners that translation is a valid tool of language learning and the necessity to teach them the skill to translate.